Preparing for the Next Harvey, Irma, or Maria — Addressing Research Gaps - Shultz, James M; Galea, Sandro (The New England journal of medicine, 2017)
Extreme events often cast in bold relief what we do and don’t know about medicine and public health. In recent weeks, Hurricanes Harvey, Irma, and Maria have illuminated our knowledge gaps regarding the consequences of disasters and their mitigation.